2019
DOI: 10.1096/fj.201802550r
|View full text |Cite
|
Sign up to set email alerts
|

Leucine‐rich repeat kinase 2 regulates mouse dendritic cell migration by ORAI2

Abstract: The leucine‐rich repeat kinase 2 (LRRK2) is expressed in various immune cells and involved in regulating inflammatory processes. LRRK2 facilitates calcium extrusion exchanger and sodium‐calcium exchanger activity and hence influences intracellular Ca2+ concentration in dendritic cells (DCs). DC maturation and migration are governed by the intracellular Ca2+ concentration, but the related mechanisms whereby LRRK2 regulates DC function and involved Ca2+ channels are still under investigation. In the previous stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…While the role of ORAI1 has widely been clarified, the contribution of the other subunits to I CRAC and SOCE emerged only later [ 28 , 33 ]. Thanks to in-depth studies on the immune system, it has elegantly been demonstrated that, in mouse T cells, ORAI2 forms heteromeric channels with ORAI1 and contributes to a reduced Ca 2+ permeation through I CRAC [ 35 , 39 ]. A negative role for ORAI2 on Ca 2+ entry was already postulated following overexpression studies in HEK293 cells [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the role of ORAI1 has widely been clarified, the contribution of the other subunits to I CRAC and SOCE emerged only later [ 28 , 33 ]. Thanks to in-depth studies on the immune system, it has elegantly been demonstrated that, in mouse T cells, ORAI2 forms heteromeric channels with ORAI1 and contributes to a reduced Ca 2+ permeation through I CRAC [ 35 , 39 ]. A negative role for ORAI2 on Ca 2+ entry was already postulated following overexpression studies in HEK293 cells [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas STIM1 and ORAI1 proteins have been deeply investigated [ 32 ], the same does not hold true for STIM2, ORAI2 and ORAI3 [ 28 , 33 ]. Only recently has the ORAI2 functionality in the immune system started to be well understood [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Conversely, in the nervous system, the role of SOCE role and its components remain obscure [ 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…In line with our findings, PTK6 promotes cancer cell aggressiveness ( 38 , 39 ). LRRK2 is also involved in inflammatory response and cell migration ( 40 , 41 ). Taken together, our data suggest that increased LINK-A promotes PTK6- and LRRK2-mediated HIF-1α protein expression and subsequently regulates aggressiveness and inflammation of RA FLSs.…”
Section: Discussionmentioning
confidence: 99%
“…LRRK2 is a key regulator protein also in dendritic cells, which are antigen-presenting cells (APC), playing an important role in Treg maturation. In more detail, LRRK2 influences cell migration through the modulation of ORAI2, which cooperates with calcium channels in the regulation of calcium efflux, necessary for cell homeostasis [ 24 ].…”
Section: Lrrk2mentioning
confidence: 99%